2016
DOI: 10.18632/oncotarget.14005
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herb cinobufagin-reduced cancer pain is associated with increased peripheral opioids by invaded CD3/4/8 lymphocytes

Abstract: ObjectivesTo investigate the mechanism of cinobufagin-reduced cancer pain in mouse cancer pain model and in vitro cell co-culture system.MethodsFemale Kunming mice were randomly divided into 4 groups. One group of animals was set as normal control without any treatment. Other three groups of animals received H22 hepatoma cell inoculation in right hind paw. At day 9 after inoculation, mice in other three groups were injected intraperitoneally once a day for 8 days with the solvent, morphine or cinobufagin, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…Moreover, the antinociceptive effect of Bufonis venenum or bufalin was blocked by the pretreatment with the opioid receptor antagonist naloxone or its peripheral form naloxone methiodide [9,10,74]. These studies suggested that Bufonis venenum and its effective ingredients produced antinociception through the β-endorphin/opioid receptor pathway [9,10].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Moreover, the antinociceptive effect of Bufonis venenum or bufalin was blocked by the pretreatment with the opioid receptor antagonist naloxone or its peripheral form naloxone methiodide [9,10,74]. These studies suggested that Bufonis venenum and its effective ingredients produced antinociception through the β-endorphin/opioid receptor pathway [9,10].…”
Section: Introductionmentioning
confidence: 94%
“…The CRF receptor was associated with microglial expression of β-endorphin [8,33,40] and Bufonis venenum stimulated CRF expression [9,10]. Thus, the possible involvement of the CRF receptor in cinobufagin-induced mechanical antiallodynia was finally tested.…”
Section: Activation Of the α7-nachr Mediated Cinobufagininduced Spinamentioning
confidence: 99%
See 3 more Smart Citations